(untitled) - Block, Peter (Hoboken, New Jersey, 2017)
Empowerment produces the conditions for high performance - especially for middle managers and below. Empowered cultures attract and retain talent. They produce high achievement, high accountability and high commitment. This volume uncovers a roadmap to creating a more accountable culture in today's fragmented and virtual world.
Keywords: Hành vi tổ chức,Organizational behavior